Between the ideal and the real: Shiite purism and the dilemma of modernity in Iraq - Abbas, Akeel (Rowman & Littlefield, 2024)
"This book deals with the Islamic Shia version of purism as the cornerstone of its faith, showing how this purism manifested itself in the story of Iraq as a state and Shias as a group of people by complicating the process of integrating the latter into the former"--